Acupuncture Treatment for Low Back Pain and Lower Limb Symptoms—The Relation between Acupuncture or Electroacupuncture Stimulation and Sciatic Nerve Blood Flow - Inoue, Motohiro (Oxford University Press, 2008)
To investigate the clinical efficacy of acupuncture treatment for lumbar spinal canal stenosis and herniated lumbar disc and to clarify the mechanisms in an animal experiment that evaluated acupuncture on sciatic nerve blood flow. In the clinical trial, patients with lumbar spinal canal stenosis or herniated lumbar disc were divided into three treatment groups; (i) Ex-B2 (at the disordered level), (ii) electrical acupuncture (EA) on the pudendal nerve and (iii) EA at the nerve root. Primary outcome measurements were pain and dysesthesia [evaluated with a visual analogue scale (VAS)] and continuous walking distance. In the animal study, sciatic nerve blood flow was measured with laser-Doppler flowmetry at, before and during three kinds of stimulation (manual acupuncture on lumber muscle, electrical stimulation on the pudendal nerve and electrical stimulation on the sciatic nerve) in anesthetized rats. For the clinical trial, approximately half of the patients who received Ex-B2 revealed amelioration of the symptoms. EA on the pudendal nerve was effective for the symptoms which had not improved by Ex-B2. Considerable immediate and sustained relief was observed in patients who received EA at the nerve root. For the animal study, increase in sciatic nerve blood flow was observed in 56.9% of the trial with lumber muscle acupuncture, 100% with pudendal nerve stimulation and 100% with sciatic nerve stimulation. Sciatic nerve stimulation sustained the increase longer than pudendal nerve stimulation. One mechanism of action of acupuncture and electrical acupuncture stimulation could be that, in addition to its influence on the pain inhibitory system, it participates in causing a transient change in sciatic nerve blood blow, including circulation to the cauda equine and nerve root.